Status Anak dari Hubungan Luar Kawin Antara WNA dengan WNI Ditinjau dari Hukum Perdata Internasional - Bunga Aldila Putri; Fandhika Al Khairi; Yusuf Taufiqurahman; Yuanita Fatma Anisa F; Deni Kurniawan (Jurnal Relasi Publik, 2023)
The meeting of foreign elements resulted from a relationship between foreign citizens (WNA) and Indonesian citizens (WNI) which resulted in the occurrence of International Private Law. Until now, the problem that can occur due to the existence of these two elements is regarding the status of children from extramarital relationships between foreigners and Indonesian citizens. This will happen because there are many considerations regarding the child's status, such as the laws of the country where the child was born and the laws of the country where both parents come from. There are a number of countries that adopt the jus soli principle, which means that the child will be considered a citizen of the country where he was born. This is different from other countries that apply the jus sanguinis principle, which means that the child will obtain citizenship status from one or both parents, regardless of where the child was born. Seeing this problem, this research discusses the status of the child if this occurs because a relationship is not registered as a marriage relationship. Then there is another discussion regarding the distribution of inheritance if the marriage relationship is not recorded. In this research, the method applied is the normative juridical method by looking at existing data and presenting it descriptively. It is hoped that with this research readers will be able to understand and add information related to the research.